The Role Of Corporate Governance In Achieving The Quality Of Accounting Information In Jordan - Al-Omari, Ahmad Ibrahim Mansi (2008)
In this study was trying to explain how the application of corporate governance in Jordan helps to maximize the performance of companies. Also, the application of corporate governance was trying to find laws and regulations that help to reduce conflicts of interest of others, materially and morally unacceptable. This study argues that there were moral link between the application of corporate governance and the quality of accounting information. And there was a moral link between the quality of accounting information for companies that applied corporate governance movement and trading in the stock market, share prices of these companies. The importance of study to emphasize the importance of expanding the application of the concept of corporate governance in the economic environment and benefit from Jordan in the development of accounting practice and development of the audit profession and thus achieve the quality of accounting information in environmental accounting of Jordan, which reflected the decisions of investors and the Jordanian stock market. Finally the results of the study showed that the accounting information variables were important in determining the factors influencing the company corporate governance.